The influence of leadership, work environment, organisational commitment with job satisfaction as an intervening variable on the work motivation of employees of the regional financial and asset management agency in Karimun District - Suganda, Muhammad Ibnu (Global Academy of Business Studies, 2025)
Purpose: Purpose: This study aimed to analyze the influence of leadership, work environment, and organizational commitment on job satisfaction, with work motivation serving as an intervening variable among employees of the Regional Financial and Asset Management Agency in Karimun Regency. Research methodology: This study employed a quantitative approach with a survey design. The population consisted of 134 employees, and 119 were selected as the sample, comprising civil servants and contract-based government employees. Data were collected through questionnaires and analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) to test both direct and indirect relationships among variables. Results: The findings show that leadership, work environment, and organizational commitment significantly influence job satisfaction. Leadership style, organizational support, and conducive conditions are the key determinants. Motivation acts as a mediating variable, strengthening the indirect effects of leadership and work environment on satisfaction, while organizational commitment shows no significant indirect effect through motivation. Conclusions: Effective leadership, supportive environments, and strong commitment boost job satisfaction, with motivation mediating the improvement of performance and effectiveness. Limitations: This study’s scope is limited; future research should use longitudinal designs and include factors like organizational culture and technology Contribution: This study enriches public sector HR literature and guides local governments in improving leadership, work environment, commitment, motivation, and satisfaction.